4D-Printed fiber-reinforced liquid crystal elastomer composites for multifunctional soft robots with self-heating actuation - Daokang Zhang; Xiaoyong Tian; Yanli Zhou; Dichen Li (Virtual and Physical Prototyping)
Fabrication of flexible actuators with precise deformability, self-heating actuation, and flexibility remain challenging due to limited mechanical properties, sensitivity to ambient temperature, and complexities in multi-material integration. In this study, continuous fibre-reinforced 4D printing technology was employed to fabricate self-heating actuators with precisely controllable deformation characteristics. The integration of continuous carbon fibres not only enhances the mechanical properties of the structure but also enables self-heating through the electrothermal effect of the carbon fibres. By adjusting the applied current, controllable temperatures and deformation curvatures can be achieved, and the thermal response can be achieved within 20 s with a maximum deformation curvature of 0.25 mm−1. Building on this foundation, we drew inspiration from the locomotion patterns of octopuses and inchworms to design a multi-legged soft robot capable of multiple movement modes. The independent control of each leg allows the soft robot to move in all directions, grasping objects weighing up to 20 times its own weight, and moving on 20° inclined surfaces. This study highlights the self-heating deformation capabilities of continuous fibre-reinforced liquid crystal elastomer actuators, showcasing their potential for use in multifunctional soft robotics applications.